2020
DOI: 10.1021/acs.est.0c03392
|View full text |Cite
|
Sign up to set email alerts
|

Low-Energy Method for Water-Mineral Recovery from Acid Mine Drainage Based on Membrane Technology: Evaluation of Inorganic Salts as Draw Solutions

Abstract: In this work, a novel study for acid mine drainage remediation and reutilization by means of a forward osmosis technology is addressed. The proposed process is a potential alternative path, which allows to recover high-quality water and to concentrate metals for its possible reutilization as synthetic minerals. This novel process will help in the mining industry evolving toward more sustainable processes and favors circular economy policies. Four inorganic salts (NaCl, KCl, CaCl 2 , and MgCl 2 ) were evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 52 publications
1
6
0
Order By: Relevance
“…It is a separation of supernatant (sludge) from treated wastewater/permeates/by the application vacuum suction force that draws the water through the membrane. It involves the application of the suction force and the flow permeates across a membrane into a separate channel for recovery, while the supernatant is retained on the membrane surface (Baena‐Moreno et al., 2020). After settling of sludge, trans‐membrane suction pressure −25 to −300 mbar is applied to separate the liquid wastewater from the solid sludge through Micro‐ or Ultrafiltration (MF/UF) membrane openings which provide perfect retention of microscopic solid particles (Robles et al., 2012).…”
Section: Membrane Biological Reactors and Their Application For Metal...mentioning
confidence: 99%
“…It is a separation of supernatant (sludge) from treated wastewater/permeates/by the application vacuum suction force that draws the water through the membrane. It involves the application of the suction force and the flow permeates across a membrane into a separate channel for recovery, while the supernatant is retained on the membrane surface (Baena‐Moreno et al., 2020). After settling of sludge, trans‐membrane suction pressure −25 to −300 mbar is applied to separate the liquid wastewater from the solid sludge through Micro‐ or Ultrafiltration (MF/UF) membrane openings which provide perfect retention of microscopic solid particles (Robles et al., 2012).…”
Section: Membrane Biological Reactors and Their Application For Metal...mentioning
confidence: 99%
“…Other active treatments applied to AMD and wastewater effluents and to recover water are based on the use of membranes. Membrane technologies have significant advantages; their operation is simple; they can be integrated with other processes to improve the yield of the recovery; and they presents low energy consumption (Cho et al, 2012;Rodríguez-Galán et al, 2019;Baena-Moreno et al 2020). In addition, membranes allow for obtaining high-quality water recovery.…”
Section: Introductionmentioning
confidence: 99%
“…Selection of the draw solute is one of the most important factors in the regeneration process (López et al, 2021;Chekli et al, 2012;Ge et al, 2013;Achilli et al, 2010;Hamdan et al, 2015). Baena-Moreno et al (2020) have studied the use of different inorganic salts with ultrapure water and acid mine drainage as feed solution (Baena-Moreno et al, 2020). Through experimental tests, they have demonstrated that magnesium chloride and calcium chloride afford the highest water fluxes and thus the highest water recovery per unit of area with the same molarity.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with traditional pressure-driven processes, FO has been proposed for treating complex wastewaters, including saline wastewater [ 45 , 46 ], industrial wastewater with high salt concentrations from oil and gas [ 2 ], mining and metallurgy [ 47 ], and cooling tower blowdown [ 48 ], streams that need to be concentrated such as liquid food [ 34 , 49 ], sludge [ 50 ], and nuclear wastewaters [ 51 ]. In general, they can be summarized into two types of applications: general applications that require draw solutes regeneration and special applications without the need for draw solutes recovery ( Figure 3 ).…”
Section: Introductionmentioning
confidence: 99%